Phytohormonal Regulation of Biomass Allocation and Morphological and Physiological Traits of Leaves in Response to Environmental Changes in Polygonum cuspidatum - Sugiura, Daisuke; Kojima, Mikiko; Sakakibara, Hitoshi (Frontiers in Plant Science, 2016)
Plants plastically change their morphological and physiological traits in response to environmental changes, which are accompanied by changes in endogenous levels of phytohormones. Although roles of phytohormones in various aspects of plant growth and development were elucidated, their importance in the regulation of biomass allocation was not fully investigated. This study aimed to determine causal relationships among changes in biomass allocation, morphological and physiological traits, and endogenous levels of phytohormones such as gibberellins (GAs) and cytokinins (CKs) in response to environmental changes in Polygonum cuspidatum. Seedlings of P. cuspidatum were grown under two light intensities, each at three nitrogen availabilities. The seedlings grown in high light intensity and high nitrogen availability (HH) were subjected to three additional treatments: defoliating half of the leaves (Def), transferral to low nitrogen availability (LowN) or low light intensity (LowL). Biomass allocation at the whole-plant level, morphological and physiological traits of each leaf, and endogenous levels of phytohormones in each leaf and shoot apex were measured. Age-dependent changes in leaf traits were also investigated. After the treatments, endogenous levels of GAs in the shoot apex and leaves significantly increased in Def, decreased in LowN, and did not change in LowL compared with HH seedlings. Among all of the seedlings, the levels of GAs in the shoot apex and leaves were strongly correlated with biomass allocation ratio between leaves and roots. The levels of GAs in the youngest leaves were highest, while the levels of CKs were almost consistent in each leaf. The levels of CKs were positively correlated with leaf nitrogen content in each leaf, whereas the levels of GAs were negatively correlated with the total non-structural carbohydrate content in each leaf. These results support our hypothesis that GAs and CKs are key regulatory factors that control biomass allocation, leaf morphology, and photosynthesis in response to changes in environmental variables in P. cuspidatum.